Analysis and Impact of Online Celebrity Brand Equity on Purchase Intention of Fans on Social Media - Utomo, Mohammad Burhan; Hidayat, Anas (Archives of Business Research, 2022)
This research aims to determine the impact of online celebrity brand equity on purchase intention of fans on social media. The testing used 250 respondents. The sampling technique used purposive sampling. This research used Structural Equation Modeling (SEM) Analysis tool which was developed to test research hypotheses which was processed by using AMOS version 24. The variables used in this research were brand awareness, brand image, brand loyalty, purchase intention, and perceived quality. The results of the analysis indicated that brand awareness had positive and significant effect on brand image, brand awareness had positive and significant effect on brand loyalty, brand image had positive and significant effect on brand loyalty, brand loyalty had positive and significant effect on purchase intention, brand loyalty that supported purchase intention will be stronger with perceived quality.